EVALUATION OF SPIRITUALITY FOR THE MAINTENANCE OF MENTAL HEALTH OF THE ELDERLY IN DIFFERENT CONTEXTS, FOR COMPARATIVE PURPOSES, IN THE MUNICIPALITY OF ANÁPOLIS - GOIÁS (CIPEEX, 2026)
Introduction: Spirituality has proven to be an important resource in facing emotional challenges during aging, being associated with the re-signification of life and adaptation to situations of vulnerability. In this context, it has become relevant to understand its role in senescent life in different settings. Objective: To evaluate the impact of spirituality on the mental health of older adults in active and non-active aging. Method: Qualitative study with individuals over 60 years old, cognitively autonomous, linked to UniAPI (UniEVANGÉLICA) and long-term care institutions (ILPIs) in Anápolis-GO. Data collection was carried out through semi-structured interviews and the GDS-15 and FACIT-sp scales, prioritizing well-being and privacy in a reserved environment. Results: Most participants showed negative results for depression (77.5%), while 17.5% had mild depression and 5% moderate depression. No significant differences were found between institutions. However, an association between spirituality and depressive symptoms was observed: high levels of spirituality were related to the absence of depression, while low levels were associated with mild or moderate conditions. Conclusion: Spirituality proved to be central in maintaining mental health, assisting in the adaptation to the challenges of aging, and reinforcing its value in the comprehensive care of the elderly.
Keywords: Aging; Spirituality; psycol